Evaluasi Implementasi Sistem Manajemen Mutu ISO 9001:2008 di Puskesmas Wilayah Kabupaten Sleman - Sri Nuryati (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
This study is a mixed method research, a combination of quantitative and qualitative research methods with cross sectional study design. Quantitative research methods to describe the implementation of QMS ISO 9001: 2008. The bureaucratic reform policy QMS ISO 9001: 2008 in health centers, a strong reason to rehabilitate physical structures all health centers. Aspects of the process: Organizational Management Aspect outcomes: The quality objectives is an indicator of success, implementation of QMS ISO 9001: 2008. QMS ISO improves customer satisfaction, the implementation of QMS ISO 9001: 2008 in health centers 48% criteria, the criteria of no less than 8%. The big difference in perceptions of health centers and the Department of Health. in health centers already meet the requirements of clause 8 in the implementation of QMS ISO 9001: 2008.